The hidden gender-based violence and associated factors among marginalised women in Southern Ethiopia - Zemenu Yohannes Kassa; Nebiha Hadra; Dejene Hailu (Elsevier, 2023)
Background: Domestic violence is a common public health concern that violates human rights in all societies. This aimed to assess domestic violence and associated factors among housemaid night students in Hawassa city. Methods: An institutional-based cross-sectional study was implemented from 1 February to 30 March 2019 among housemaid night students in Hawassa city. A stratified, two-stage cluster sampling technique was used. Finally, the study population was selected from the respective source population using a simple random sampling technique (computer-generated random numbers were used). Data were checked, coded and entered into Epi data version 3.1.5 and exported to SPSS version 20 for analysis. Bivariate and multivariable analyses were computed to identify the determinants of domestic violence among housemaid night students. Result: In this study, the housemaid experienced at least one form of domestic violence was 20.9 %(95% CI: 17.9, 24.2). Whereas 16.9% (95% CI: 14.0, 20.0) experienced physical violence, 9.7% were slapping, and the current employer performed 9% of any domestic violence among housemaid night students. Besides, 11% (95% CI: 8.7, 13.5) experienced sexual violence, 4% attempted rape, and the employer's son/friends performed 5.7% of sexual violence among housemaid night students. Conclusion: Employer family size, any habit like khat chewing and drinking alcohol, anyone who watches pornography in the employer's home, anyone who enforces the housemaid to watch pornography, and lack of knowledge of domestic violence is higher odds of domestic violence among housemaid night students. Hence, the labour and social affairs and concerned stakeholders could create awareness about domestic violence for housemaids, families, and employers.